Vitamin A source variability: a mini review on stability and bioavailability in poultry - Shastak, Yauheni; Pelletier, Wolf (Frontiers in Animal Science, 2024)
Vitamin A is essential for poultry health, influencing vision, growth, antioxidant defense, reproduction, and immune function. However, it is highly sensitive to degradation when exposed to light, moisture, heat, and oxygen. To address this, vitamin A is typically formulated as retinyl acetate in small beadlets. These beadlets are commonly included in premixes for industrial poultry diets. However, variations in beadlet formulations among different producers can lead to differences in stability and bioavailability, potentially impacting their effectiveness and biological value for poultry. Understanding the stability and bioavailability of various vitamin A sources is crucial for optimizing poultry feeding strategies and ensuring adequate vitamin A supply. The stability of vitamin A can be evaluated through several methods, including premix stability, stability during pelleting, storage stability in feed, and the stability of pure vitamin A products. Bioavailability, which reflects how effectively vitamin A is absorbed and utilized by the animal, is typically assessed through in vivo studies, with liver retinol levels serving as a key indicator. To enhance poultry production, it is important to select vitamin A sources that offer both high stability and bioavailability. Effective feed management, including the use of stable and readily absorbed forms of vitamin A, can improve poultry health, growth rates, and overall production efficiency.